2023
DOI: 10.1038/s42255-023-00814-x
|View full text |Cite
|
Sign up to set email alerts
|

CaMK1D signalling in AgRP neurons promotes ghrelin-mediated food intake

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Many studies have reported that ghrelin mediates appetite and feeding behavior through AgRP/NPY neurons. 34 Our findings suggest that, in ABA mice, altered ghrelin levels in the duodenum may, to some extent, influence or be influenced by brain neuro-metabolism, activating hormonal circuitries to help the body recover from the negative energy balance. However, it is also possible that factors other than peripheral ghrelin contributed to these brain-related outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…Many studies have reported that ghrelin mediates appetite and feeding behavior through AgRP/NPY neurons. 34 Our findings suggest that, in ABA mice, altered ghrelin levels in the duodenum may, to some extent, influence or be influenced by brain neuro-metabolism, activating hormonal circuitries to help the body recover from the negative energy balance. However, it is also possible that factors other than peripheral ghrelin contributed to these brain-related outcomes.…”
Section: Discussionmentioning
confidence: 72%